2020
DOI: 10.1186/s12906-020-2827-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tannase-converted green tea extract on skeletal muscle development

Abstract: Background: The aim of this study was to investigate the effect of tannase-converted green tea extract with a high (−)-epicatechin (EC), (−)-epigallocatechin (EGC), and gallic acid (GA) content on myotube density and fusion in normal and oxidative stress-induced C2C12 skeletal muscle cells. Although the use of green tea extract is considered beneficial, cellular and molecular mechanisms of action of tannase-converted green tea extracts that are used as potential muscle growth materials have not been thoroughly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The results obtained in this study suggest that green tea extract improves muscle mass and strength potentially by influencing myostatin levels. These observations are consistent with previous results from our group showing that EC administration resulted in a significant increase in the expression of muscle differentiation genes, such as myoblast determination protein (MyoD) and myogenin genes in stressed C2C12 muscle cells [20]. The levels of factors related to muscle degradation or loss, such as forkhead box protein O3 (FOXO3), myostatin, muscle RING finger protein-1 (MuRF-1), and atrogin-1, were also significantly reduced by treatment with green tea extract with a high EC content in aged mice [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained in this study suggest that green tea extract improves muscle mass and strength potentially by influencing myostatin levels. These observations are consistent with previous results from our group showing that EC administration resulted in a significant increase in the expression of muscle differentiation genes, such as myoblast determination protein (MyoD) and myogenin genes in stressed C2C12 muscle cells [20]. The levels of factors related to muscle degradation or loss, such as forkhead box protein O3 (FOXO3), myostatin, muscle RING finger protein-1 (MuRF-1), and atrogin-1, were also significantly reduced by treatment with green tea extract with a high EC content in aged mice [21].…”
Section: Discussionsupporting
confidence: 93%
“…The use of tannase-treated green tea extract containing a high content of EC and GA has been reported to improve skeletal muscle recovery [20,21]. However, whether such beneficial effects occur in humans without added exercise is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, reported that Epi promotes myogenic differentiation in C2C12 cells by increasing the protein levels of MyoD, myogenin leading to increases in MHC 51 . Epi also increased SkM mRNA levels of MyoD and decreased the expression of FoxO3, myostatin and MuRF1 53 . Si et al 54 reported that Epi increases the survival rate of aged mice and delays SkM degeneration.…”
Section: Discussionmentioning
confidence: 91%
“…It also upregulated mitochondrial biogenesis, oxidative phosphorylation, myosin heavy chain (MyHC) content, autophagy/mitophagy, and the fusion/fission index of mitochondria in C2C12 myotubes [ 29 ]. Gallic acid (GA) in combination with epicatechin (EC) and epigallocatechin (EGC) increased muscle differentiation by inducing the myogenic regulatory factors myogenin, Myf5, and MyoD in C2C12 myotubes [ 30 ]. Another compound of this class, ellagic acid, exerts antioxidant, anti-inflammatory, anticancer, hypolipidemic, and neuroprotective effects [ 31 ].…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…In this review, we reported several compounds that enhance mitochondrial functions by increasing mitochondrial biogenesis or reducing mitochondrial dysfunction [ 29 , 36 , 56 , 74 , 78 , 79 , 105 , 125 ]. Furthermore, several polyphenolic compounds were found to stimulate myogenesis for the growth and differentiation of muscle cells [ 30 , 71 , 81 , 146 ]. Thus, for future antiatrophic treatment, both the catabolic/anabolic modulators and mitochondrial bioenergetics will be useful therapeutic targets.…”
Section: Critical Overview and Future Perspectivesmentioning
confidence: 99%